Recycling of carbon fibers from unsaturated polyester composites via a hydrolysis-oxidation synergistic catalytic strategy. (8th February 2021) - Wang, Baolong; Wang, Xinyu; Xu, Ningdi; Shen, Yibo; Lu, Fei; Liu, Yingying; Huang, Yudong; Hu, Zhen
Abstract: Unsaturated polyester resins (UPRs) composites have many industrial applications, such as fan blades in wind energy. However, the stable cross-linked polymer networks of resin matrix lead to large numbers of composite wastes that are difficult to recycle. Developing an efficient approach to explore the recovery of high-value fiber from composites is thus imperative. In this paper, an efficient and mild hydrolysis-oxidation synergistic catalytic strategy was proposed to efficiently recycle carbon fibers from UPRs composites by selectively cleaving chemical bonds of UPRs. Ester bonds in UPRs were cleaved by using hydrolysis of 80% hydrazine hydrate along with NaOH. Afterwards, the cleavage of carbon-carbon bonds was accomplished via the Fenton reaction for the purpose of complete degrading UPRs. The result figured that UPRs could be efficiently degraded at 100 °C below via this hydrolysis-oxidation strategy. Interestingly, applying the strategy, the recovery of carbon fibers from UPRs composites was investigated. The reclaimed carbon fibers kept their original surface microscopic morphology, chemical structure and tensile strength almost close to the virgin carbon fibers. This strategy opens up a new way for efficient and mild degradation of thermosets. Graphical abstract: Image 1 Highlights: An efficient hydrolysis-oxidation synergistic catalytic strategy was developed for degrading UPRs. The thermoset UPRs could be efficiently degraded under mild conditions. The recovery of the CFs from UPRs composites was explored.